Why performativity limits credit rating reform - Bart Stellinga (Finance and Society, 2019)
The 2008 crisis made clear that credit rating agencies (CRAs) can contribute to systemic financial risk. Surprisingly, post-crisis reforms have hardly addressed the underlying problems, including rating agencies' methodologies, their ratings' homogeneity, and widespread market reliance on these signals. Current scholarship on CRA regulation blames policymakers' unwillingness to fix systemic problems. This article draws on insights from the social studies of finance literature to provide a different explanation: the key obstacle is policymakers' inability to fix these problems. The regulatory problem stems from performativity: risk assessments (including ratings) shape the risks they purport to merely describe. Adding to this literature, the article spells out how performativity limits credit rating reforms by making sweeping changes potentially harmful. Standardizing methodologies or setting up a public CRA could reinforce ratings' homogeneity. Replacing ratings in regulation with market-based indicators might create worse systemic problems. The article then empirically details how EU policymakers, confronted with these dilemmas, ultimately steered clear of bold reforms.
Keywords: 300; Credit rating agencies; performativity; regulation; financial crisis; systemic risk; procyclicality